Pengembangan Media Pembelajaran Interaktif Berbasis Microsoft Power Point Untuk Materi Invers Matriks - Cicilia Puji Rahayu (Universitas Veteran Bangun Nusantara, 2023)
Learning media is one of the renewal models of the lecture model learning process. For this reason, researchers developed learning media for Inverse Matrix material based on Microsoft power point as a renewal of learning methods. The purpose of developing learning media using power point is so that it can be used without having to install an application specifically, made with a capacity that is not large, but complete, clearly to increase student understanding and achievement. This learning media has been tested for feasibility by experts in the fields of mathematics and multimedia. The test results by experts in the field of mathematics concluded that the material met the syllabi standard in inverse matrix material, while the test results by multimedia experts showed that the appearance was attractive, simple, clear navigation and feasible to implement.